Characterization of an evolutionarily conserved far-upstream enhancer in the human alpha 2(I) collagen (COL1A2) gene. - Antoniv, T; De Val, S; Wells, D; Denton, C; Rabe, C; de Crombrugghe, B; Ramirez, F; Bou-Gharios, G (2001)
We have examined the chromatin structure around and upstream of the transcriptional start site of the human alpha2(I) collagen (COL1A2) gene. Four strong DNase I-hypersensitive sites (HS2-5) were only detected in fibroblasts, and a weaker one (HS1) was identified in type I collagen-negative cells. Another hypersensitive site potentially involved in COL1A2 silencing was found in intron 1 (HS(In)). HS1 and HS2 were mapped within conserved promoter sequences and at locations comparable to the mouse gene. HS3, HS4, and HS5 were likewise mapped approximately 20 kilobases upstream of COL1A2 at about the same position as the mouse far-upstream enhancer and within a remarkably homologous genomic segment. DNase I footprinting identified twelve areas of nuclease protection in the far-upstream region (FU1-12) and within stretches nearly identical to the mouse sequence. The region containing HS3-5 was found to confer high and tissue-specific expression in transgenic mice to the otherwise minimally active COL1A2 promoter. Characterization of the human element documented functional differences with the mouse counterpart. Enhancer activity substantially decreased without the segment containing FU1-7 and HS5, and inclusion of AluI repeats located 3' of HS3 augmented position-independent expression of the transgene. Hence, subtle differences may characterize the regulation of mammalian alpha2(I) collagen genes by evolutionarily conserved sequences.